2015
DOI: 10.5805/sfti.2015.17.2.216
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Risk of Up-cycling Fashion Product on Trust, Purchase Intention and Recommendation Intention

Abstract: : This study identifies factors of perceived risk of up-cycling fashion products and investigates perceived risk factors that influence consumers' trust, purchase intention, and recommendation intention towards upcycling fashion products. We also examine the relationship of trust, purchase intention, and recommendation intention for upcycling fashion products. A qualitative research method using a free narrative form and depth interview were used. The perceived risk from up-cycling fashion products generated 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Compared to earlier research on perceived risks, these five anxiety factors are distinct empirical classifications of perceived fashion risk [45]. In terms of the perceived risks of circular fashion, Park and Choo [46] conducted a qualitative study to derive the perceived risk dimension of upcycled fashion products, and identified five dimensions: aesthetic, sanitary, social, performance, and economic risk. Kim and Kim [47] also suggested that diversity risk and performance risk are two fundamental dimensions of perceived risk of upcycled products, while Yoon [28] proposed performance risk, economic risk, and social psychological risk as perceived risks of reused and recycled clothing.…”
Section: Circular Fashion and Consumers' Perceived Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to earlier research on perceived risks, these five anxiety factors are distinct empirical classifications of perceived fashion risk [45]. In terms of the perceived risks of circular fashion, Park and Choo [46] conducted a qualitative study to derive the perceived risk dimension of upcycled fashion products, and identified five dimensions: aesthetic, sanitary, social, performance, and economic risk. Kim and Kim [47] also suggested that diversity risk and performance risk are two fundamental dimensions of perceived risk of upcycled products, while Yoon [28] proposed performance risk, economic risk, and social psychological risk as perceived risks of reused and recycled clothing.…”
Section: Circular Fashion and Consumers' Perceived Riskmentioning
confidence: 99%
“…In the current study, we classified the risk dimensions of circular fashion based on Park and Choo [46] since they took a similar stance to ours Among their five risk perception dimensions, social risk (i.e., anxiety about being judged by others about the design and appearance of recycled clothing) was excluded because it somewhat overlapped with the explanation of aesthetic risk and because several studies have shown that it is not associated with word of mouth (WOM) intention and purchase intention. Thus, we divided consumers' perceived risks of circular fashion into financial, functional, aesthetic, and sanitary risk in this study, and supported each risk dimension with reference to previous studies.…”
Section: Circular Fashion and Consumers' Perceived Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Customers can continue to benefit from metaverse experiences after trips, where benefits signify the desired outcomes from consumption (Choe and Kim, 2018;Kim and Choe, 2019;Park et al, 2023) . The third theme of customer benefits encompasses three categories (epistemic, social, and emotional) driven by metaverse applications.…”
Section: Customer Benefitsmentioning
confidence: 99%
“…Studies show that most customers perceive upcycled fashion products as overpriced [61,62]. Niinimaki, et al [63] suggested that consumers should view fashion as a functional product and be willing to pay more for environmentally conscious products.…”
Section: Price Perceptionmentioning
confidence: 99%